The relation between simulated multiwavelength blazar variability and stochastic fluctuations - Thiersen, Hannes; Zacharias, Michael; Böttcher, Markus (The astrophysical journal, 2024)
Blazars exhibit multiwavelength variability, a phenomenon whose underlying mechanisms remain elusive. This study investigates the origin of such variability through leptonic blazar emission simulations, focusing on stochastic fluctuations in environmental parameters. By analyzing the spectral indices of the power spectral densities of the variability, we assess their relationship with the underlying fluctuations. Our findings reveal that the variability spectral indices remain almost independent of the variations responsible for their emergence. This suggests a complex interplay of factors contributing to the observed multiwavelength variability in blazars.